Optical properties and artistic color characterization of nanocomposite polyurethane materials - Hu Jiaju; Zhang Youqiang (Science and Engineering of Composite Materials)
Nanocomposite polyurethane (PU) materials have broad application prospects in the fields of optics and artistic colors, but there are few systematic studies on the application of nano-titanium dioxide (TiO₂), nano-zinc oxide (ZnO), and nano-silver (Ag) in PU matrices. The aim of this study is to prepare a PU matrix with the same transmittance but better UV absorption by adding these nanoparticles to improve the optical properties and UV resistance of the material. In this study, the solution method was used to prepare and characterize nano-TiO2, ZnO and Ag particles, and their addition amount and dispersion state were precisely controlled to prepare composite materials with different mass fractions. The properties of these composites were comprehensively evaluated by UV-visible spectroscopy analysis, transmission electron microscopy observation, and color measurement methods. The results showed that nano-TiO₂ significantly improved the transparency and UV blocking ability of the material, nano-ZnO enhanced the UV stability, and nano-Ag improved the transparency, antibacterial properties, and color stability. The specific data are as follows: the transmittance of nano-TiO2 and ZnO dropped from 85 to 55%, respectively, and the transmittance of nano-Ag dropped from 90 to 60%; in terms of ultraviolet absorption rate, nano-TiO2 increased from 10 to 45%, ZnO increased from 15 to 50%, and Ag increased from 20 to 55%. In addition, the study evaluated the effects of UV irradiation on the optical properties and color stability of the nanocomposites and found that the addition of nanoparticles significantly improved the material’s resistance to UV aging. In summary, the kind and location of nanoparticles have a substantial impact on the properties of PU composites. This study provides a scientific basis for the creation of high-performance nanocomposite PU materials.